Search for flavor-changing-neutral-current D meson decays - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2008)
We study the flavor-changing-neutral-current process c→uμ+μ- using 1.3fb-1 of pp̄ collisions at s=1.96TeV recorded by the D0 detector operating at the Fermilab Tevatron Collider. We see clear indications of the charged-current mediated Ds+ and D+→ π+→μ+μ-π+ final states with significance greater than 4 standard deviations above background for the D+ state. We search for the continuum neutral-current decay of D+→π+μ+μ- in the dimuon invariant mass spectrum away from the resonance. We see no evidence of signal above background and set a limit of B(D+→π+μ+μ-)<3.9×10-6 at the 90% C.L. This limit places the most stringent constraint on new phenomena in the c→uμ+μ- transition. © 2008 The American Physical Society.